Wykrywanie współliniowości za pomocą scentrowanych, niescentrowanych oraz uogólnionych czynników inflacji wariancji - Dudek, Hanna (Detecting of Collinearity by Using Centered, Noncentered and Generalized Variance Inflation Factors, 2005)
In this article we analyze the concepts of variance inflation factors VIF. Centered VIF is misleading in the case of small variation of one of the regressors. In such cases noncentered VIF should be applied. In order to determine collinearity for a set of related regressors, such as dummy regresssors corresponding to a categorical variable, generalized inflation factor is applied. Moreover explanatory variables selection methods are analyzed in the context of collinearity. We demonstrate that by using Hellwig's method and Bartosiewicz's method it is possible to choose variables with linearly dependent vectors of observations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 613-622